Short-Run and Long-Term Effects of Childbirth on Mother's employment and working hours across institutional regimes : an empirical analysis based on the European community household panel - Johannes Geyer; Viktor Steiner (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
The employment behavior of mothers is strongly influenced by labor market regulations and certain institutional arrangements, which both vary greatly across European countries. Using the European Community Household Panel (ECHP) 1994-2001 for Denmark, Germany, Italy and the United Kingdom, which represent four distinct ?institutional regimes?, we estimate the short-run and long-term effects of childbirth on married women?s employment and working hours. Estimation results show that these effects vary across the four countries in accordance with prevailing institutional regulations.
Keywords: D12; J13; J22; 330; employment and working hours; labor supply; childbirth; European Community Household Panel; panel data models; Frauenerwerbstätigkeit; Mütter; Arbeitsangebot; Familienpolitik; Mutterschutz; Vergleich; Dänemark; Deutschland; Italien; Großbritannien